Conservation of Geomorpological Heritage in the Homolje Area (Eastern SERBIA) - Current State and Perspectives - Đurđa Miljković; Ljupče Miljković; Mlađen Jovanović (Geoconservation Research)
Homolje is one of the most developed geomorphological areas in Eastern Serbia. Shallow karsts prevail across this region with cover vegetation and soil, with developed surfaces, and underground karst landforms. This type of terrain leads to the occurrence of different geomorphological landforms that stand out from the rest, primarily for their scientific, aesthetic and ecological value, uses, and tourism potential. Gorges can be singled out as the largest geosites, then uvalas, caves, karst bridges, and tufa accumulations. Two are on the National list of geoheritage of Serbia as protected natural monuments. As geoheritage protects only authentic and representative landforms, the main task of this paper is to point out the most significant measures to improve the unsatisfactory current state of geomorphosites of the Homolje area and possible solutions for their conservation, adequate use and better tourism promotion. This paper presents a review of geomorphological heritage in this region of Serbia with a focus on its conservation.